The Relationship Of Entrepreneurial Mindset And Entrepreneurial Passion To Entrepreneurial Intention Through Entrepreneurial Attitude As An Intervening Variable - Prayoga, Bhima Erlangga Sukma; Soetjipto, Budi Eko; Sumarsono, Hadi (International Education Trend Issues, 2023)
This study aims to determine the effect of an entrepreneurial mindset and passion for entrepreneurship on entrepreneurial intentions through entrepreneurial attitudes in vocational students in Sooko Mojokerto. The results of this study indicate that the Entrepreneurial Mindset is proven to have a positive and significant influence on the Entrepreneurial Attitude. Similarly, the Entrepreneurial Mindset and Entrepreneurial Passion are each proven to have a positive and significant influence on student entrepreneurial intention. This study also successfully tested the mediator role of Entrepreneurial Attitude on the relationship between Entrepreneurial Mindset and Entrepreneurial Passion to Entrepreneurial Intention. The test results show the effect of an entrepreneurial mindset on entrepreneurial intention can be mediated by an entrepreneurial attitude. In addition, the role of entrepreneurial attitude is also proven to mediate the effect of entrepreneurial passion on student entrepreneurial intention. Thus, the Entrepreneurial Attitude variable shows its role in mediating the independent variables in this study by increasing the effect of Entrepreneurial Mindset and Entrepreneurial Passion on students` Entrepreneurial Intention